Využití umělé inteligence pro snižování rizika v podniku - Samohýl, Lukáš (Vysoké učení technické v Brně. Ústav soudního inženýrství, 2016)
Tato diplomová práce se zabývá analýzou rizik sortimentu suchých krmiv pro psy řetězce maloobchodních prodejen Zvěrokruh. Cílem práce je za pomoci fuzzy logiky navrhnout model, který na základě vyhodnocení kvality produktu pomůže s vyhodnocením rizik prodejního sortimentu. Model je vyhotoven v MS Excel a MATLAB. Výstupem práce je nástroj, který vyhodnotí kvalitu zkoumaného krmiva, které pak lze podrobit dalším analýzám.

This diploma thesis is focused on risk analysis of dry dog food range of products sold in a retail chain named Zvěrokruh. The main goal of this work is creation of model with use of the fuzzy logic. The model helps with the dry dog food range risk evaluation. The model is created in MS Excel and MATLAB. Outcome of this work is a tool which evaluate quality of the dry dog food, which can be afterwards analysed in other point of view.
The Use of Artificial Intelligence to Reduce the Risk in the Firm
Keywords: Fuzzy logika; Excel; MATLAB; riziko; suché krmivo pro psy.; Fuzzy logic; Excel; MATLAB; risk; dry dog food.